Response of borderline resectable pancreatic cancer to neoadjuvant therapy is not reflected by radiographic indicators - Katz, Matthew H. G.; Fleming, Jason B.; Bhosale, Priya; Varadhachary, Gauri; Lee, Jeffrey E.; Wolff, Robert; Wang, Huamin; Abbruzzese, James; Pisters, Peter W. T.; Vauthey, Jean‐Nicolas; Charnsangavej, Chusilp; Tamm, Eric; et al. (Cancer, 2012)
BACKGROUND: Experience with preoperative therapy for other cancers has led to an assumption that borderline resectable pancreatic cancers can be converted to resectable cancers with preoperative therapy. In this study, the authors sought to determine the rate at which neoadjuvant therapy is associated with a reduction in the size or stage of borderline resectable tumors. METHODS: Patients who had borderline resectable pancreatic cancer and received neoadjuvant therapy before potentially undergoing surgery at the authors' institution between 2005 and 2010 were identified. The patients' pretreatment and post‐treatment pancreatic protocol computed tomography images were rereviewed to determine changes in tumor size or stage using modified Response Evaluation Criteria in Solid Tumors (RECIST) (version 1.1) and standardized anatomic criteria. RESULTS: The authors identified 129 patients who met inclusion criteria. Of the 122 patients who had their disease restaged after receiving preoperative therapy, 84 patients (69%) had stable disease, 15 patients (12%) had a partial response to therapy, and 23 patients (19%) had progressive disease. Although only 1 patient (0.8%) had their disease downstaged to resectable status after receiving neoadjuvant therapy, 85 patients (66%) underwent pancreatectomy. The median overall survival duration for all 129 patients was 22 months (95% confidence interval, 14‐30 months). The median overall survival duration for the patients who underwent pancreatectomy was 33 months (95% confidence interval, 25‐41 months) and was not associated with RECIST response (P = .78). CONCLUSIONS: Radiographic downstaging was rare after neoadjuvant therapy, and RECIST response was not an effective treatment endpoint for patients with borderline resectable pancreatic cancer. The authors concluded that these patients should undergo pancreatectomy after initial therapy in the absence of metastases. Cancer 2012. © 2012 American Cancer Society. The authors re‐evaluate the pancreatic protocol computed tomography scans obtained before and after neoadjuvant therapy from 129 patients who had borderline resectable pancreatic cancer. In this cohort, only 1 patient had disease downstaged radiographically to potentially resectable after treatment, but 85 patients underwent pancreatectomy, and response according to Response Evaluation Criteria in Solid Tumors was not associated with overall survival after resection.